Synthesis of quinine N-oxide and an NMR tutorial in its structure determination - Aisyah Aisyah; Nila Berghuis Tamaela; Joko Santoso; Yana Maolana Syah; Didin Mujahidin (Jurnal Penelitian Teh dan Kina, 2014)
Cinchona alkaloids are one of abundant natural chiral pool for organocatalysts. The application of an N-oxide group containing molecule in asymmetric reaction is currently wide developed. The structure of quinine consist two amine groups that could be oxidized to the N-oxide groups at N-1â€™ of quinoline and at N-1 of quinuclidine moieties. The oxidation reaction took place selectively at quinuclidine moiety by controlling the concentration of oxidizing agents. In this study we showed that N-1-oxide quinine could be occurred chemoÂselectively by using a low concentration of ozone thana palladium catalyzed oxidation. The structure of products N1-oxide quinine was elucidated by spectroscopy data including 1H-NMR, 13C-NMR, 2D-NMR, infra-red and mass spectrometry. The developed method is a chemoselectively and eco-friendly method for synthesis N1-oxide quinine.